Health Education on Pregnant Women's Gymnastics at the Murni Midwife Clinic, North Padang Lawas Regency - Harahap, Ica Fauziah; Bella, Cindya; Habidah, Habidah; Helmalia, Helmalia; Pohan, Melia Sintia Mutiara (IJCS: International Journal of Community Service, 2024)
This community service is themed "Health Education on Prenatal Gymnastics as an effort to increase knowledge of pregnant women about the implementation of Prenatal Gymnastics. The purpose of this activity is to provide knowledge about the processprepare the mother's physical condition by maintaining the condition of the muscles and joints that play a role in the birthing processamong pregnant women to carry out proper handling. The implementation of this activity is planned in 3 stages, namely the preparation stage, the implementation stage, and the evaluation stage. The preparation stage includes processing permits, collecting initial data in the form of assessments by providingpretestto pregnant women about prenatal gymnastics, preparation of tools and materials, and coordination with related parties. The implementation stage of the activity is to conduct health education about the process of prenatal gymnastics, to carry out its management. The evaluation stage is to conduct Prenatal Gymnastics Education and prepare a report on the results of health education given to pregnant women. From the results of interviews, several pregnant women revealed that after participating in health education, they gained very useful knowledge that had never been obtained before and was important to be able to practice in everyday life. Based on the evaluation results, it shows an increase in the level of knowledge of pregnant women about prenatal health education.